2021
DOI: 10.3390/epidemiologia2030021
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Delayed Vaccination Regimens: A Mathematical Modeling Approach

Abstract: The first round of vaccination against coronavirus disease 2019 (COVID-19) began in early December of 2020 in a few countries. There are several vaccines, and each has a different efficacy and mechanism of action. Several countries, for example, the United Kingdom and the USA, have been able to develop consistent vaccination programs where a great percentage of the population has been vaccinated (May 2021). However, in other countries, a low percentage of the population has been vaccinated due to constraints r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 167 publications
(278 reference statements)
4
13
0
Order By: Relevance
“… 72 An estimated rise in the transmission rate is high and it is found in multiple other states of the United States. 73 , 74 It has L452R mutation in S protein which was discovered in the RBD. It increases infectivity because of the interaction between spike protein and ACE2 receptors.…”
Section: Variants Of the Sars‐cov‐2mentioning
confidence: 99%
“… 72 An estimated rise in the transmission rate is high and it is found in multiple other states of the United States. 73 , 74 It has L452R mutation in S protein which was discovered in the RBD. It increases infectivity because of the interaction between spike protein and ACE2 receptors.…”
Section: Variants Of the Sars‐cov‐2mentioning
confidence: 99%
“…Thus, an optimal vaccination campaign needs to consider the aforementioned factors. The governments of the USA and the UK have implemented different vaccination strategies, and some researchers have been investigating the optimal vaccination programs [47][48][49][50][51]. It has been found that the vaccination rate and the efficacy of the vaccine are the main factors in reducing some health outcomes, such as number of deaths, number of infected and hospitalizations [25,44,45,[52][53][54].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in [53] the author found that an incidence-minimizing vaccination strategy is highly sensitive to vaccine efficacy, and vaccines with lower efficacy should be administered to teenagers and adults aged 50-59 years. Some researchers have studied the effects of delayed second doses on important health outcomes, such as death [6,48,50,51,55].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations